2017
DOI: 10.1002/jcp.26073
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potentials of adenosine receptors agonists and antagonists in colitis; Current status and perspectives

Abstract: Increasing evidence suggests that adenosine is dysregulated in ulcerative colitis (UC), potentially affecting UC pathogenesis, diagnosis, and therapy. Dysregulation of the activity of adenosine generating enzymes including adenosine deaminase in serum of patients with acute colitis supports the role of this omnipresent metabolite in the pathogenesis of colitis. Adenosine regulates inflammatory responses including epithelial barrier hyper-permeability, myeloperoxidase activity, and neuromuscular motility in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 86 publications
0
7
0
1
Order By: Relevance
“…Adenosine as an omnipresent metabolite is involved in different processes, and any dysregulation in the generation of this molecule could contribute to the pathogenesis of certain diseases from cancer [2,41] to inflammatory disorders. [42,43] Recently, adenosine and its receptors attracted tremendous attention in cancer pathology and provide new research area in therapy purposes. Increased level of adenosine in tumour microenvironment regulates tumour growth by modulating tumorigenic processes including angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine as an omnipresent metabolite is involved in different processes, and any dysregulation in the generation of this molecule could contribute to the pathogenesis of certain diseases from cancer [2,41] to inflammatory disorders. [42,43] Recently, adenosine and its receptors attracted tremendous attention in cancer pathology and provide new research area in therapy purposes. Increased level of adenosine in tumour microenvironment regulates tumour growth by modulating tumorigenic processes including angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore vital to find new therapeutics to attenuate complications of the disease. Recently, adenosine and its analogs have emerged as potential therapeutic agents for treatment of numerous conditions from cancers to inflammatory diseases (Bahreyni, Samani, Khazaei, et al, ; Bahreyni et al, ). Consistently, there are several studies showing that both A2a and A2b ADORs are expressed in cardiovascular tissues and modulation of these receptors by adenosine or pharmacological molecules plays key roles in the regulation of heart rate, blood pressure, and heart rate variability in the cardiovascular system (Thomas et al, ; Vecchio, White, & May, ).…”
Section: Discussionmentioning
confidence: 99%
“…The CD39/CD73/A2a adenosine metabolic pathway plays an important role in the immune tolerance function of Treg cells. Studies have shown that patients with UC have lower adenosine levels, and the use of adenosine receptor A2a agonist can effectively reduce colitis and inhibit the production of proinflammatory factors [ 85 , 86 ]. Zhuang et al [ 87 ] found that the fluorescence intensity, the number of positive cells, and protein expression of CD39, DC73, and A2a in the colon of DSS mice increased after acupuncture.…”
Section: Acupuncture Exerts Immunomodulatory Effects By Regulating Adaptive Immune Systemmentioning
confidence: 99%